2022
DOI: 10.1155/2022/4450196
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mesoporous Silica Nanoparticle-Chitosan-Loaded BMP-2 in the Repair of Bone Defect in Chronic Osteomyelitis

Abstract: In order to test the effectiveness of nanoparticle- (NP-) loaded bone morphogenetic protein 2 (BMP-2) in chronic osteomyelitis (CO) complicated with bone defect, a new nanodrug delivery system composed of mesoporous silica NP (MSN) and chitosan were used to load BMP-2 and transfer it to the target region. Bone marrow mesenchymal stem cells (BMSCs) were purchased and cultivated to detect the osteogenesis of chitosan-MSN (Chi-MSN) and polylactic acid glycolic acid (PLGA) delivery system. In addition, the osteoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…148−150 Delivery systems equipped with proteins are instead prepared using mild methods such as low-temperature freeze-drying or coprecipitation, although these traditional methods may result in uneven coating thickness. 151 The adhesion of the coating depends on the chemical bond between the scaffold and NPs, surface free energy, cleanliness, roughness, and other factors. Therefore, chemical modification of the scaffold surface is often achieved through the use of acids or oxidants, which can increase surface polarity and thus improve the adhesive strength of the coating.…”
Section: Construction Strategies Of Np-based Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…148−150 Delivery systems equipped with proteins are instead prepared using mild methods such as low-temperature freeze-drying or coprecipitation, although these traditional methods may result in uneven coating thickness. 151 The adhesion of the coating depends on the chemical bond between the scaffold and NPs, surface free energy, cleanliness, roughness, and other factors. Therefore, chemical modification of the scaffold surface is often achieved through the use of acids or oxidants, which can increase surface polarity and thus improve the adhesive strength of the coating.…”
Section: Construction Strategies Of Np-based Drug Delivery Systemsmentioning
confidence: 99%
“…However, the physical and chemical properties of therapeutic factors inside the carrier must be fully considered, as some coating preparation conditions can easily lead to their deactivation, especially for protein drugs such as growth factors. Therefore, the electrostatic layer-by-layer self-assembly method using strong acid or strong alkali treatment and the vapor deposition method using high-temperature treatment are not considered suitable for a delivery system of protein molecules. Delivery systems equipped with proteins are instead prepared using mild methods such as low-temperature freeze-drying or coprecipitation, although these traditional methods may result in uneven coating thickness …”
Section: Construction Strategies Of Np-based Drug Delivery Systemsmentioning
confidence: 99%
“…[70] For example, the delivery of mesoporous silica nanoparticles (MSN) significantly improves the stability of BMP-2 and reduces its loss during in vivo transport. [71] Similarly, Atefyekta et al synthesized mesoporous titanium dioxide films with different pore sizes (4, 6, and 7 nm) and loaded them with three different antibiotics (vancomycin, gentamicin, and daptomycin), which could be successfully loaded and released from the surface. The results of counting bacterial colony-forming units showed reduced in bacterial adhesion to the loaded films.…”
Section: Porous Materials and Amp-based Conjugation Therapymentioning
confidence: 99%
“…The release and delivery of bone morphogenetic protein 2 (BMP-2) are critical for improving the clinical efficacy of bone healing and repair. To transfer BMP-2 to the target area, Yi et al (2022) constructed a novel nano-delivery system (Chi-MSN) composed of mesoporous silica nanoparticles (MSN) and chitosan. The study reported that the Chi-MSN system could effectively reduce drug loss and deliver BMP-2 to the lesion site due to its stable and pH-responsive properties.…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…FIGURE 4Mesoporous Silica Nanoparticle-Chitosan-Loaded BMP-2 in the Repair of Bone Defect in Chronic Osteomyelitis. Reproduced with permission fromYi et al (2022). Copyright © 2022 The Authors.…”
mentioning
confidence: 99%